Multi-level benchmark system for sustainability reporting: EU experience for Ukraine - Inna Makarenko; Serhiy Makarenko (Accounting and Financial Control, 2023)
The paper analyzes the key European benchmarks in the field of compiling and submitting sustainability reports. The analysis concerns the disclosure of their features in the context of considering the introduction in Ukraine to increase transparency, accountability and investment attractiveness of Ukrainian enterprises. Based on content and comparative analyses, a comparison was made of the key provisions of sustainability reporting issued by various standards-setters (ISSB (International Sustainability Standards Board), EFRAG (European Financial Reporting Advisory Group), SEC (The United States Securities and Exchange Commission), GRI (Global Reporting Initiative), and IIRC (International Integrated Reporting Council)) as a methodological level of the system of such benchmarks. The global impact of the specified benchmarks is complemented by an analysis of the impact of Directive 2014/95/EU (Non-Financial Reporting Directive – NFRD) and the new Directive 2022/2464/EU (Corporate Sustainability Reporting Directive – CSRD) on the introduction of the sustainability reporting. It is proved that in the context of the formation of the Ukrainian accounting system on the way to European integration, the transposition of the requirements of these Directives is the first step towards streamlining the regulatory framework for companies’ sustainability reporting. A two-level sustainability reporting benchmark system is presented, which at the operational level is based on the EU directives on disclosure of non-financial information and sustainability reporting, and at the methodological level – on the European Sustainability Reporting Standards and other generally accepted standards. Acknowledgment Inna Makarenko gratefully acknowledges support from the Supreme Council of Ukraine (0122U201796).